2008
DOI: 10.1177/0272989x07312714
|View full text |Cite
|
Sign up to set email alerts
|

The Cost-Effectiveness of Counseling Strategies to Improve Adherence to Highly Active Antiretroviral Therapy among Men Who Have Sex with Men

Abstract: Objective-Inadequate adherence to highly active antiretroviral therapy (HAART) may lead to poor health outcomes and the development of HIV strains that are resistant to HAART. We developed a model to evaluate the cost effectiveness of counseling interventions to improve adherence to HAART among men who have sex with men (MSM).Methods-We developed a dynamic compartmental model that incorporates HIV treatment, adherence to treatment, and infection transmission and progression. All data estimates were obtained fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(57 citation statements)
references
References 135 publications
1
52
0
4
Order By: Relevance
“…Counselling to improve adherence to HAART has been shown to increase length of life and modestly reduce HIV transmission (Zaric et al, 2008). The respondents in this study showed, with varied responses, that counselling does affect adherence to HAART:…”
Section: Counsellingmentioning
confidence: 87%
See 2 more Smart Citations
“…Counselling to improve adherence to HAART has been shown to increase length of life and modestly reduce HIV transmission (Zaric et al, 2008). The respondents in this study showed, with varied responses, that counselling does affect adherence to HAART:…”
Section: Counsellingmentioning
confidence: 87%
“…Counselling to improve adherence to HAART has been shown to increase length of life and modestly reduce HIV transmission (Zaric et al, 2008). The same study by Zaric and 48 colleagues (2008) also showed that counselling can provide significant benefit for individual patients, where there are limited resources, at an affordable cost.…”
Section: Social Supportmentioning
confidence: 96%
See 1 more Smart Citation
“…La bibliografía alrededor del modelado matemático de la transmisión del VIH y del SIDA es amplia, pero algunos modelos planteados en la literatura se han enfocado en el modelado de la infección y el tratamiento se citan algunos trabajos interesantes (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15).…”
unclassified
“…• availability of appropriate counselling (Knobel et al, 1999;Zaric, Bayoumi, Brandeau, & Owens, 2008);…”
Section: Adherence To Highly Active Antiretroviral Therapy: Barriers mentioning
confidence: 99%